Clinical effectiveness and predictors of response to topiramate plus lifestyle modification in youth with obesity seen in a weight management clinical setting - Bomberg, Eric M.; Clark, Justin; Rudser, Kyle D.; Gross, Amy C.; Kelly, Aaron S.; Fox, Claudia K. (Frontiers in Endocrinology, 2024)
Introduction Obesity affects approximately 20% of U.S. youth. Anti-obesity medications (AOMs) are promising lifestyle modification adjuncts for obesity treatment, and topiramate is commonly prescribed in pediatric weight management clinics. It is important to determine “real-world” effectiveness of AOMs and, given shifts towards personalized approaches, characteristics potentially predicting better or worse response. We therefore sought to describe clinical effectiveness from topiramate plus lifestyle modification, and to determine if baseline phenotypic characteristics are associated with better or worse response. Methods We performed a retrospective cohort study (2012-2020) among youth (<18 years old) followed in a U.S. academic-based weight management clinic. Baseline characteristics (i.e., body mass index (BMI), liver function tests, eating-related behaviors) and outcomes (%BMI of 95th percentile (%BMIp95), BMI, percent %BMI change, weight) were determined through review of electronic health records and clinic intake survey data. Results Among 282 youth prescribed topiramate plus lifestyle modifications (mean baseline age 12.7 years, %BMIp95 144%), %BMIp95 and percent BMI change were statistically significantly reduced at each time point (1.5-, 3-, 6-, and 12-month %BMIp95 reductions: -2.2, -3.9, -6.6, and -9.3 percentage points, respectively; percent BMI reduction: -1.2%, -1.9%, -3.2%, and -3.4%, respectively; all p<0.01). Considering multiple comparisons, no baseline characteristics statistically significantly predicted response at any time point. Conclusions We found that topiramate plus lifestyle modification reduced %BMIp95 and BMI among youth in a weight management clinical setting, and that no baseline characteristics evaluated were associated with response. These results should be considered preliminary given the observational nature of this study, and prospective studies are needed to further characterize clinical effectiveness and identify and confirm potential predictors of response.